Outcomes of Posterolateral Fusion with and without Instrumentation and of Interbody Fusion for Isthmic Spondylolisthesis: A Prospective Study. (3rd May 2017) - Endler, Peter; Ekman, Per; Möller, Hans; Gerdhem, Paul
Abstract : Background: Various methods for the treatment of isthmic spondylolisthesis are available. The aim of this study was to compare outcomes after posterolateral fusion without instrumentation, posterolateral fusion with instrumentation, and interbody fusion. Methods: The Swedish Spine Register was used to identify 765 patients who had been operated on for isthmic spondylolisthesis and had at least preoperative and 2-year outcome data; 586 of them had longer follow-up (a mean of 6.9 years). The outcome measures were a global assessment of leg and back pain, the Oswestry Disability Index (ODI), the EuroQol-5 Dimensions (EQ-5D) Questionnaire, the Short Form-36 (SF-36), a visual analog scale (VAS) for back and leg pain, and satisfaction with treatment. Data on additional lumbar spine surgery was searched for in the register, with the mean duration of follow-up for this variable being 10.6 years after the index procedure. Statistical analyses were performed with analysis of covariance or competing-risks proportional hazards regression, adjusted for baseline differences in the studied variables, smoking, employment status, and level of fusion. Results: Posterolateral fusion without instrumentation was performed in 102 patients; posterolateral fusion with instrumentation, in 452; and interbody fusion, in 211. At 1 year, improvement was reported in the global assessment for back pain by 54% of the patients who had posterolateral fusion without instrumentation, 68% of those treated with posterolateral fusion with instrumentation, and 70% of those treated with interbody fusion (p = 0.009). The VAS for back pain and reported satisfaction with treatment showed similar patterns (p = 0.003 and p = 0.017, respectively), whereas other outcomes did not differ among the treatment groups at 1 year. At 2 years, the global assessment for back pain indicated improvement in 57% of the patients who had undergone posterolateral fusion without instrumentation, 70% of those who had posterolateral fusion with instrumentation, and 71% of those treated with interbody fusion (p = 0.022). There were no significant outcome differences at the mean 6.9-year follow-up interval. There was an increased hazard ratio for additional lumbar spine surgery after interbody fusion (4.34; 95% confidence interval [CI] = 1.71 to 11.03) and posterolateral fusion with instrumentation (2.56; 95% CI = 1.02 to 6.42) compared with after posterolateral fusion without instrumentation (1.00; reference). Conclusions: Fusion with instrumentation, with or without interbody fusion, was associated with more improvement in back pain scores and higher satisfaction with treatment compared with fusion without instrumentation at 1 year, but the difference was attenuated with longer follow-up. Fusion with instrumentation was associated with a significantly higher risk of additional spine surgery. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.